P008 A QUALITATIVE STUDY OF THE PATIENT EXPERIENCE OF PAIN AND PAIN-RELATED FUNCTIONAL IMPACTS SPECIFIC TO CROHN'S DISEASE. (18th January 2018) - Skalicky, Anne; Gleeson, Sara; Naegeli, April; Kleinman, Leah
Abstract: Background: Crohn's disease (CD) is a chronic inflammatory gastrointestinal (GI) disorder that may involve any site of the GI tract. CD is characterized by intestinal and extra intestinal manifestations. Symptoms include persistent diarrhea and pain. Pain symptoms can range from slight discomfort to severe pain and can be episodic with symptom flare-ups that can have impacts on daily life. The objective of this study was to understand pain symptoms and related impacts specific to CD. Methods: Patients diagnosed with moderate to severe CD were recruited from 5 clinical sites in the United States for a qualitative study to elicit experiences and impacts of CD pain symptoms including severity, frequency, variability, importance, and bother. One-on-one telephone interviews were conducted using a semi-structured interview guide. A content analysis approach was used to analyze transcripts using coding dictionaries and ATLAS.ti software. Results: A total of 20 adults with CD participated in the interviews. The majority of participants were female (65%), with mean age of 42.6 years. Average time since CD diagnosis was 11 years. Frequently reported pain-related symptoms included abdominal pain (100%), abdominal discomfort (100%), abdominal cramping (90%), pain with diarrhea (90%), and uncomfortable or painful bloating (85%). Over half of participants (55%) experienced extra-abdominal pain including in their joints, back, and whole body pain. Generally, abdominal and extra-abdominal pain symptoms were worse during a flare-up in terms of severity, frequency, and duration. Pain was related to impacts on physical function (100%), emotional (85%), medical treatment (65%), work (60%), social/leisure (55%), role function (50%), quality of life (45%), and school (40%). Conclusion: Pain-related symptoms experienced by adults with moderate to severe CD are abdominal and extra-abdominal. Pain as a result of CD has significant impact on physical function aspects of patients' lives.